Promosi Kesehatan Mental Remaja Melalui Virtual Boothcamp Untuk Meningkatkan Peer-Support - Nisa, Haiyun; Aidina, Wenny; Rahmita, Nanda Rizki; Manita, Erlis; Auliani, Fitri (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Mental health is an important issue in adolescent development because during adolescence there is a more complex and dynamic transition. Conflict with peers and family is a source of interpersonal stress for adolescents. However, at the same time, family and peers can also be the main source of support as an effort to prevent stress, especially during the COVID-19 pandemic. To create mentally healthy teenagers, it is necessary to identify potential strategies, one of which is a virtual bootcamp program involving peers. The aim of this program is to promote mental health and improve peer-support capabilities for teenagers so that it is hoped that it can help create mentally healthy teenagers. The material provided is related to general issues regarding mental health; responses and actions related to adolescent mental health; self-healing; peer-support; and self-care. Participants consisted of 50 people with an age range of 15-27 years old, male and female. The effectiveness of implementing activities is known from the results of evaluating reactions and knowledge through pretests and posttests of training participants. The results of data analysis show that there is an increase in knowledge regarding peer-support and the skills possessed by adolescents to maximize their role as friends and promote mental health among their peers. It is hoped that this service article can provide information regarding the importance of adolescent mental health promotion programs, especially in overcoming the various pressures faced by adolescents.